2022
DOI: 10.1071/wr21091
|View full text |Cite
|
Sign up to set email alerts
|

Increasing fire severity negatively affects greater glider density

Abstract: Context Fire severity and frequency is predicted to increase over the remainder of the 21st century in Australia’s temperate forests; therefore, the effects of fire severity on forest-dependant species is of major conservation concern. Aims Determining the short-term (<1 year) effect of fire severity on a forest-dependant species, the greater glider, Petauroides volans, in Monga National Park, south-eastern New South Wales. Methods Three fire-severity classes were investigated, namely, low (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…2015; May‐Stubbles et al . 2022). Our results demonstrate that high‐severity fires can have lasting effects on the greater glider, even in these highly fire‐resilient, resprouting eucalypt forests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; May‐Stubbles et al . 2022). Our results demonstrate that high‐severity fires can have lasting effects on the greater glider, even in these highly fire‐resilient, resprouting eucalypt forests.…”
Section: Discussionmentioning
confidence: 99%
“…2015; May‐Stubbles et al . 2022), as well as parts of landscapes that remain long unburnt (>30 years; McLean et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Greater gliders are extremely susceptible to population decline and extinction, particularly in response to fire that partially or completely consumes the canopy 97 . Lindenmayer et al 36 reported low greater glider abundances in high severity burn sites in the Central Highlands of Victoria, and May-Stubbles et al 37 observed the same pattern within high severity burn sites of Monga National Park, NSW. This is due to the species' specialist eucalypt diet and sensitivity to high temperatures [29][30][31]37,45,98 .…”
Section: Baseline Genetic Data Following Firementioning
confidence: 91%
“…Lindenmayer et al 36 reported low greater glider abundances in high severity burn sites in the Central Highlands of Victoria, and May-Stubbles et al 37 observed the same pattern within high severity burn sites of Monga National Park, NSW. This is due to the species' specialist eucalypt diet and sensitivity to high temperatures [29][30][31]37,45,98 . Fire has also caused significant declines in the past, with greater gliders considered locally extinct after a fire burnt 90% of the Royal National Park (NSW) before they were rediscovered in 2012 99 .…”
Section: Baseline Genetic Data Following Firementioning
confidence: 91%
See 1 more Smart Citation